(x^2-5xy)(-3xy) (2x^3-3x^2+x+30):(x+2) (x+3)^2+(7-x)^2+2(x+3)(7-x) giùm mình đi nha các bạn

By Sadie

(x^2-5xy)(-3xy)
(2x^3-3x^2+x+30):(x+2)
(x+3)^2+(7-x)^2+2(x+3)(7-x)
giùm mình đi nha các bạn

0 bình luận về “(x^2-5xy)(-3xy) (2x^3-3x^2+x+30):(x+2) (x+3)^2+(7-x)^2+2(x+3)(7-x) giùm mình đi nha các bạn”

  1. `(x^2-5xy)(-3xy)`

    `=x^2.(-3xy)-5xy.(-3xy)`

    `=-3x^3 y+15x^2 y^2`

    `(2x^3-3x^2+x+30):(x+2)`

    `=(2x^3+4x^2-7x^2-14x+15x+30):(x+2)`

    `=[2x^2(x+2)-7x(x+2)+15(x+2)]:(x+2)`

    `=(x+2)(2x^2-7x+15):(x+2)`

    `=2x^2-7x+15`

    `(x+3)^2+(7-x)^2+2(x+3)(7-x)`

    `=(x+3+7-x)^2`

    `=10^2`

    `=100`

    Trả lời

Viết một bình luận